Beckett on film : 19 films x 19 directors. (Sl : Blue Angel Films, 2001)
Contents: Disk 1 Red (1. Waitng for Godot / Michael Lindsay-Hogg.-- 2. Not I / Neil Jordan.-- 3. Rough for theatre I / Kieron J. Walsh.-- 4 Ohio impromptu / Charles Sturridge.-- 5. Docummentary.-- 6. Addenda.) Disk 2 Blue (1. Krapp's last tape / Atom Egoyan.-- 2. What where / Damien O'Donell.-- 3. Come and go / John Crowley.-- 4. Act without words I / Karel Reisz.-- 5. Addenda.) Disk 3 (1. Happy days / Patricia Rozema.-- 2. Catastrophe / David Mamet.-- 3. Rough theatre II / Katie Mitchell.-- 4. Breath / Damien Hirst.-- 5. That time / Charles Garrad.-- 6. Addenda.) Disk 4 Purple (1. End game / Conor McPherson.-- 2. Act without words II / Edna Hughes.-- 3. A piece of monolouge / Robin Lefevre.-- 4. Play / Anthony Minghella.-- 5. Rockaby / Richard Eyre.-- 6. Addenda.)
The comprehensive cinematic iterpretation od Bekett's plays.